2022
DOI: 10.3389/fenrg.2022.942314
|View full text |Cite
|
Sign up to set email alerts
|

High-entropy spinel-structure oxides as oxygen evolution reaction electrocatalyst

Abstract: High-entropy oxides are an upcoming research topic due to their broad range of possible crystal structures and applications. In this work, we want to present the change in the catalytic properties when using different elements to create a high-entropy spinel. Therefore, we used the nebulized-spray pyrolysis to synthesize the high-entropy spinel (Mn0.2Fe0.2Ni0.2Mg0.2Zn0.2)3O4 and later on exchanged the Mg or the Zn with elements with multiple possible oxidation states, in our example each with Cr or Co. The pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…[1] Entropy-induced structure stabilization is also reported to be the reason for improved OER stability in comparison to binary and ternary materials possessing-at the same time-equal overpotentials. [15,66] Stenzel et al identified an optimized elemental composition for spinelstructured HEOs resulting in low overpotentials of 293 mV (at 10 mA cm −2 ). [66] With respect to HEOs, photocatalytic hydrogen production, [67] photoelectrochemical water reduction [23] and oxidation [68] have rarely been studied, showing up to date only low to moderate photocurrents and hydrogen evolution efficiencies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1] Entropy-induced structure stabilization is also reported to be the reason for improved OER stability in comparison to binary and ternary materials possessing-at the same time-equal overpotentials. [15,66] Stenzel et al identified an optimized elemental composition for spinelstructured HEOs resulting in low overpotentials of 293 mV (at 10 mA cm −2 ). [66] With respect to HEOs, photocatalytic hydrogen production, [67] photoelectrochemical water reduction [23] and oxidation [68] have rarely been studied, showing up to date only low to moderate photocurrents and hydrogen evolution efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…[15,66] Stenzel et al identified an optimized elemental composition for spinelstructured HEOs resulting in low overpotentials of 293 mV (at 10 mA cm −2 ). [66] With respect to HEOs, photocatalytic hydrogen production, [67] photoelectrochemical water reduction [23] and oxidation [68] have rarely been studied, showing up to date only low to moderate photocurrents and hydrogen evolution efficiencies. A recent study of our group on (non-ordered) mesoporous spinel HEO revealed a low photoresponse under visible light irradiation, most likely owing to structural defects induced by implementation of several cations with distinct radii.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] The entropy-induced structure stabilization effect is also reported to be the reason for improved OER stability in comparison to binary and ternary materials possessing -at the same time -equal overpotentials. [68,69] In this context, Stenzel et al identified an improved (equiatomic) elemental composition for spinel-structured HEOs resulting in low overpotentials of 293 mV (at 10 mA/cm 2 ). [69] High entropy ferrites (HEF) have recently been investigated as highperforming sulfur host material in lithium-sulfur batteries, [70] as microwave absorbing material, [71,72] and magnetic insulator, [73] however, up to now, never in the context of electrocatalytic and/or photoelectrochemical water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…[68,69] In this context, Stenzel et al identified an improved (equiatomic) elemental composition for spinel-structured HEOs resulting in low overpotentials of 293 mV (at 10 mA/cm 2 ). [69] High entropy ferrites (HEF) have recently been investigated as highperforming sulfur host material in lithium-sulfur batteries, [70] as microwave absorbing material, [71,72] and magnetic insulator, [73] however, up to now, never in the context of electrocatalytic and/or photoelectrochemical water splitting. Recently, the group of Brezesinski has reported on mesoporous ferrite films as well, however incorporating fewer types of cations and focusing on magnetic properties.…”
Section: Introductionmentioning
confidence: 99%